FEATURES OF PRIMARY DISABILITY IN PEOPLE OF DIFFERENT AGE (ON THE EXAMPLE OF THE REPUBLIC OF UZBEKISTAN) (Academicia Globe: Inderscience Research, 2022)
This paper presents an analysis of primary disability persons of working and retirement age. Studied gender differences, causes, severity of disability among people’s indifferent age. The high demand of persons with disabilities in measures of social rehabilitation.